THE ROLE OF SAVE THE CHILDREN ON THE IMPLEMENTATION OF WASH IN SCHOOL EMPOWERMENT (WISE) IN NUSA TENGGARA TIMUR - Siregar, Gary Nathanael; Harto, Syafri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Save The Children is an NGO that plays a role in protect and fight for the right of children through improvement clean water service and sanitations through the WISE programme in East Nusa Tenggara. Through the WISE Program, Save The Children also supports the implementation of the Millennium Development Goals (MDGs) for children in East Nusa Tenggara. This essay research is aiming to describe the role of Save The Children on the implementation of WASH in School Empowerment in East Nusa Tenggara on 2011-2013. Type The research by author is type descriptive-analytic, research that uses pattern depiction circumstances fact empirical accompanied relevant arguments with method research qualitative. Technique data collection is done through studies library, document and interviews, primary and secondary. The author 's perspective Use is perspective pluralism with level analysis nation-state and use theory organization international. This research shows that Save The Children plays an active role with build amenities sanitation and clean water, training health for teachers and little doctor through UKS, as well promote message hygiene in schools base in East Nusa Tenggara. Key Words: Non-Govermental Organization, Save The Children, Millenium Development Goals, WISE.